Meningkatkan Keterampilan Berbicara Anak Usia 5-6 Tahun Menggunakan Video Animasi di Raudhatul Athfal Mas’udi Kota Pontianak - Dianika Sridadi; Yuniarti Yuniarti; Diana Diana (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This research was motivated by the low level of children’s speaking ability in learning activities. This study aims to improve the speaking skills of children aged 5–6 years at Raudhatul Athfal Mas’udi and to examine how animated video learning is implemented to enhance the speaking skills of children aged 5–6 years at Raudhatul Athfal Mas’udi. The method used in this study is a qualitative method with the type of Classroom Action Research (CAR). The subjects of this study were Group B students of Raudhatul Athfal Mas’udi Pontianak, totaling 17 children. There are three aspects examined in this study, namely understanding information that is heard, repeating more complex sentences, and answering more complex questions. To obtain the data, this research used observation, interviews, and documentation. The results of the study show that children’s speaking skills before and after each cycle experienced a very good improvement. Thus, animated videos are proven to be effective in improving children’s speaking skills.